Regional peace in Latin America: a multifaceted explanation (Revista da Escola de Guerra Naval, 2023)
Since the 19th century, Latin America has progressivelybecome a zone of peace. Between 1800 and 2007, the region hasbeen affected by only fourteen inter-state wars. In addition,the frequency of inter-state wars has rapidly declined over thedecades, generating a consolidated zone of peace. This paperexamines the reasons behind regional peace in Latin America,reviewing the main theories of war and peace and assessingtheir validity in explaining the absence of inter-state warsin the region. The study finds that each one of the theoriesconsidered addresses only a single aspect of this phenomenon.Based on that, a multifaceted explanation of regional peace inLatin America is proposed, combining different theories toprovide a more complete analysis of the phenomenon. Thisexplanation presents peace in Latina America as the resultof two interacting elements: countries’ satisfaction with theirborders and the presence of weak states in the region. Whilerecognizing that political regimes can influence countries’war-proneness (and that democratic regimes tend to be lesswar-prone than authoritarian regimes), this study shows thatdemocracy is not the ultimate cause of regional peace in LatinAmerica. Indeed, the presence of authoritarian regimes in theregion did not hinder the creation of a zone of peace betweenthe 19th and 20th century. However, the study highlights thatthe spread of democracy in the region helped consolidatingthe zone of peace and determined its evolution from mereabsence of war to institutionalized security community